THE 2-PHENYLETHANOL AND ETHANOL PRODUCTION BY YEAST SACCHAROMYCES CEREVISIAE - О. Г. Мамєєва; А. М. Остапчук; В. С. Підгорський (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2010)
The present study is focused on the determination of the 2-phenylethanol and ethanol production with use of statistical analyses experiments combined with Box Behnken design under the influence of sucrose, yeast extract and L-phenylalanine concentra tions. The effect of each factor as well as their interactions was assessed by ANOVA technique. S. cerevisiae UCM Y-514 and UCM Y-524 produced the highest calculated adjusted level 1.21 g/l of 2-phenylethanol. Meanwhile, the level of ethanol reached 22.39 g/l. The regression equations derived from statistical analysis of three main effects and the models with multiple correlation coefficients were obtained.